Building a business case for agro-weather SMS services for smallholder farmers [Kenya] - Akuku, Boniface (Technical Centre for Agricultural and Rural Cooperation, 2018)
Most of the business models for weather services to smallholder farmers in Kenya are financially too unsustainable to scale-up. To do so it requires capacity building and establishing quality management system geared toward validating the impact.